Bangladesh population & housing census, 2011 : community report, Zila Bandarban. - Bangladesh. Parisankhyana Bureau (Dhaka : Bangladesh Bureau of Statistics, Statistics and Informatics Division, Ministry of Planning, Government of the People's Republic of Bangladesh, 2014)
Health and Population
Keywords: Housing -- Bangladesh -- Statistics; Bangladesh -- Population -- Statistics; Bangladesh -- Census, 2011.